2016
DOI: 10.3390/molecules21040496
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Scopoletin in Tumor Cells

Abstract: Drug resistance and the severe side effects of chemotherapy necessitate the development of novel anticancer drugs. Natural products are a valuable source for drug development. Scopoletin is a coumarin compound, which can be found in several Artemisia species and other plant genera. Microarray-based RNA expression profiling of the NCI cell line panel showed that cellular response of scopoletin did not correlate to the expression of ATP-binding cassette (ABC) transporters as classical drug resistance mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Scopoletin (6‐methoxy‐7‐hydroxycomarin) is a phenolic coumarin and an important member of the group of phytoalexins isolated from many plants . A variety of biological activities like anti‐inflammatory, anti‐allergy and anti‐angiogenesis have been reported for scopoletin, known also for its cytotoxicity towards cancer cells …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Scopoletin (6‐methoxy‐7‐hydroxycomarin) is a phenolic coumarin and an important member of the group of phytoalexins isolated from many plants . A variety of biological activities like anti‐inflammatory, anti‐allergy and anti‐angiogenesis have been reported for scopoletin, known also for its cytotoxicity towards cancer cells …”
Section: Resultsmentioning
confidence: 99%
“…43 A variety of biological activities like antiinflammatory, anti-allergy and anti-angiogenesis have been reported for scopoletin, known also for its cytotoxicity towards cancer cells. [19][20][21] In the literature, there are many different extraction techniques used to obtain artemisinin in particular from the fresh plant matrix. The methods used are generally time-consuming, needing often instruments with relatively critical purchase and operating costs, and also showing a strong environmental impact and extractive efficiency that is not always optimal ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies have reported that Moxa Coccinea has analgesic, anti-inflammatory and antioxidant effects (Jamuna et al, 2015), blood pressure lowering and antispasmodic effects, especially antitumor (Liu et al, 2012;Tabana et. al., 2016;Seo et al, 2016;Zhao et al, 2012) and its activity in the prevention and treatment of hyperuricemia (Yao et al, 2012), has currently attracted widespread attention at home and abroad. It can prevent alcohol-induced Hepatic lipid accumulation (Lee et al, 2014), insecticidal activity, acaricidal activity, antibacterial activity, growth regulation, and induction of plant resistance (Hino, Okazaki and Miura, 2014).…”
Section: Analysis Of Functionmentioning
confidence: 99%